2020
DOI: 10.1111/tct.13280
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Education on Complementary and Integrative Medicine

Abstract: The prevalence of multimorbidity is increasing with the rise in chronic diseases and the rapid ageing of the population. This has implications for all health care professions, since patient care is becoming increasingly complex and can only be optimally managed through the interaction of all professionals involved. 1 In addition, more and more patients want to add on complementary medicine to their treatment. 2 Complementary medicine refers to a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…More than 70% agreed or rather agreed that CIM at university hospitals should be an interprofessional task, with nurses more likely to agree than physicians. The high demand for interprofessionality was also expressed in a study by Homberg and Stock-Schröer, who used a qualitative approach to investigate the advantages and disadvantages of interprofessional CIM education in Germany and Switzerland ( 54 ). They concluded that an interprofessional approach could help to overcome stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…More than 70% agreed or rather agreed that CIM at university hospitals should be an interprofessional task, with nurses more likely to agree than physicians. The high demand for interprofessionality was also expressed in a study by Homberg and Stock-Schröer, who used a qualitative approach to investigate the advantages and disadvantages of interprofessional CIM education in Germany and Switzerland ( 54 ). They concluded that an interprofessional approach could help to overcome stereotypes.…”
Section: Discussionmentioning
confidence: 99%